Non-invasive Markers for Diagnosis of Liver Cirrhosis in Chronic Hepatitis B - Jeffry Beta Tenggara; Irsan Hasan; Andri Sanityoso; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Indonesia is an endemic country for hepatitis B viral infection. Thus, early diagnosis of cirrhosis is important to be established with regard to prompt treatment and to determine the patients’ prognosis. Liver biopsy which is a gold standard in diagnosing liver cirrhosis has several limitations, such as expensive and invasive. The objective of this study was to identify the accuracy of non-invasive markers: aspartate/alanine transaminase ratio (AAR), age-platelet index (API), aspartate transaminase to platelet ratio index (APRI), spleen to platelet ratio index (SPRI), and age-spleen-platelet ratio index (ASPRI) in predicting cirrhosis in chronic hepatitis B patients. Methods: A diagnostic study was performed in Division of Hepatology and Hepatology Outpatient Clinic, Depatment of Internal Medicine, Cipto Mangunkusumo Hospital between January 2009 and July 2010, with the participation of 71 chronic hepatitis B patients who had undergone liver biopsy consecutively. Stage of fibrosis was determined based on the METAVIR scoring system. Five non-invasive markers: AAR, API, APRI, SPRI, and ASPRI were compared with liver biopsy Results. Statistical analysis was performed by using T-test and Spearman correlation test using SPSS version 13. Results: API, APRI, SPRI, and ASPRI had significant correlation with the incidence of liver cirrhosis in hepatitis B infection (p 0.05). However, AAR had no correlation with the incidence of cirrhosis. Using the cut-off point of 1.19, APRI was the best marker with area under curve (AUC) 0.91, sensitivity 83.3%, and specificity 89.2%. Conclusion: Non-invasive markers were suitable in predicting cirrhosis and have the potential to decrease the number of liver biopsy in chronic hepatitis B patients. Keywords: non-invasive markers, chronic hepatitis B, liver cirrhosis